2013
DOI: 10.31729/jnma.1923
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Feeding Practices of Nepali mothers for 6 months to 24 months children.

Abstract: Introduction: Lack of knowledge and proper feeding practices contribute to higher childhood morbidity and mortality. The aim of the study wasto evaluate the mother’s knowledge and practices in terms of quantity, quality and timing of complementary feeding in infant and young child.Methods: A hospital based cross-sectional study was conducted between June, 2010 to October, 2011, at Kanti Children's Hospital, Nepal, involving 1100 mothers of children from 6 to 24 months of age who attended outpatient department … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
32
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 14 publications
11
32
2
5
Order By: Relevance
“…This finding is consistent with the study findings in India [31] and Pakistan [37]. However, this finding is higher than the study finding in Nepal [38]. …”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with the study findings in India [31] and Pakistan [37]. However, this finding is higher than the study finding in Nepal [38]. …”
Section: Discussionsupporting
confidence: 93%
“…Greater maternal education and better feeding knowledge alone are not likely to fully address poor complementary feeding practice, however (Chapagain, ). The Dalit and “other” category of sociocultural groups were less likely to meet the minimum complementary feeding criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Continued and strengthened messaging regarding the timely introduction of complementary foods may encourage exclusive breastfeeding until 6 months of age. One study in Nepal showed sufficient knowledge among mothers to be the most influential factor in regards to optimal feeding practices, and whether or not mothers received advice on IYCF practices during immunization visits was associated with appropriate feeding (Chapagain 2013). Secondary analysis of the most recent Nepal DHS revealed that mothers who attended four or more antenatal care visits were more likely to feed their children in accordance with recommended frequency (Khanal et al 2013).…”
Section: Mothers With Childrenmentioning
confidence: 99%